Akankah Sentimen Pasar Menghasilkan Keputusan Investasi yang Tepat? - Wiyasa, I Wayan Aristiya; Akob, Muh.; Sumail, La Ode (Jurnal Samudra Ekonomi dan Bisnis, 2024)
The aim of this research is to investigate the influence of market sentiment on investment decisions and the role of fundamentals and technicals as mediating variables. 259 respondents were selected using a purposive sampling technique, namely BRI Danareksa Sekuritas investors who had made transactions for at least the last 3 months. The results show that investors who have positive market sentiment can make the right investment decisions. Investors who have positive market sentiment and have the right technical analysis skills will also make the right investment decisions. However, even if you have good technical analysis but do not have complete information about the market, you will get weak or poor investment decisions. Furthermore, investors who have positive market sentiment will create the right fundamental analysis so that they will also make the right investment decisions.